2016
DOI: 10.3390/s16071024
|View full text |Cite
|
Sign up to set email alerts
|

Single-Use Disposable Electrochemical Label-Free Immunosensor for Detection of Glycated Hemoglobin (HbA1c) Using Differential Pulse Voltammetry (DPV)

Abstract: Abstract:A single-use disposable in vitro electrochemical immunosensor for the detection of HbA1c in undiluted human serum using differential pulse voltammetry (DPV) was developed. A three-electrode configuration electrochemical biosensor consisted of 10-nm-thin gold film working and counter electrodes and a thick-film printed Ag/AgCl reference electrode was fabricated on a polyethylene terephthalate (PET) substrate. Micro-fabrication techniques including sputtering vapor deposition and thick-film printing wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 28 publications
7
35
1
1
Order By: Relevance
“…The EIS study of this pretreated sensor showed excellent reproducibility as reported in our other studies. [11,12] …”
Section: Chemical Pretreatment Of the Thin Gold Film Electrode Elementsmentioning
confidence: 99%
See 2 more Smart Citations
“…The EIS study of this pretreated sensor showed excellent reproducibility as reported in our other studies. [11,12] …”
Section: Chemical Pretreatment Of the Thin Gold Film Electrode Elementsmentioning
confidence: 99%
“…The purpose of pretreatment was to minimize the electrode charge transfer resistance, thereby improving the sensitivity and the reproducibility of the sensor. This pretreatment procedure was based on other reported investigation [9,10] as well as in our own previous studies [11,12]. Typically, a batch of 8 thin gold film based sensors were immersed in a 2M KOH solution for 15min.…”
Section: Chemical Pretreatment Of the Thin Gold Film Electrode Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…This platform biosensor had been successfully used in the detection of other biomarkers, such as lysyl oxidase like-2, LOXL2, of metastasis of breast cancer (31), hemoglobin A1c, HbA1c, of diabetes (32) and T-Tau of neurodegenerative disorder (33), and the details of the fabrication of the biosensor were given elsewhere (31)(32)(33). This biosensor used a three-electrode configuration.…”
Section: Biosensor Fabricationmentioning
confidence: 99%
“…Also, there are various nanomaterials like gold nanoparticles, carbon nanotubes (CNT), Core-shell magnetic bionanoparticles, Nitrogen doped grapheme etc [71][72][73][74][75][76][77], which can be used in constructing an electrochemical sensor as well as other different type of biosensors for example microfluidic, optical for the detection of glycated hemoglobin. So a comparison of nanomaterials based sensing devices for the detection of HbA1c has also been briefed in Table 3.…”
Section: Electrochemical Biosensor For Glycated Hemoglobin (Hba1c)mentioning
confidence: 99%